2015
DOI: 10.1002/aelm.201500036
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Polymer Thin Film Transistor Performance by Carefully Controlling the Solution Self‐Assembly and Film Alignment with Slot Die Coating

Abstract: Polymer‐based organic semiconductors inherently facilitate solution processing and have the mechanical robustness necessary for printable and large area applications. In order to achieve large area solution‐processed high‐performance polymer based devices, controlling the crystallization and self‐assembly behavior of the polymer thin films through solution processing method is desirable. Here, well controlled diketopyrrolopyrrole‐thieno[3,2‐b]thiophene copolymer (DPPT‐TT) thin films are developed using slot di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Moreover, the higher planar DPP‐based conjugated backbones exhibit better intrachain and interchain charge transport . Besides the delicate polymer design, directly aligning the D–A conjugated backbones toward the source and drain electrodes is an appealing strategy for improving electrical performance . Therefore, developing a facile and efficient approach to realize the oriented polymer thin film is in a demand.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, the higher planar DPP‐based conjugated backbones exhibit better intrachain and interchain charge transport . Besides the delicate polymer design, directly aligning the D–A conjugated backbones toward the source and drain electrodes is an appealing strategy for improving electrical performance . Therefore, developing a facile and efficient approach to realize the oriented polymer thin film is in a demand.…”
mentioning
confidence: 84%
“…Solution‐coating techniques capable of fabricating oriented polymer thin films, such as brush‐painting, solution shearing, slot die coating,[8a] bar coating,[8b] dip coating,[8c] off‐center spin coating, and directional drying have been vigorously developed. Using these techniques, the conjugated polymer backbone alignment is proceeded under the directional stress (the directional shearing force, the centrifugal force, and the gradient evaporation force), which is aroused by the directional fluid flow, with controlling the durations for self‐assembly of polymer chains.…”
mentioning
confidence: 99%
“…The estimated pep stacking distance was 0.37 nm. This is similar to most of DPP based conjugated polymers [17,38].…”
Section: Resultsmentioning
confidence: 56%
“…Among these methods, slot die coating has been proved to be a simplistic and manufacturable approach to fabricate large area high performance field effect transistors. Most importantly, it was found that this method is not only suitable for small molecule system like TIPS-pentacene [24], but also useful for polymer systems like diketopyrrolopyrrole-thieno[3,2-b]thiophene copolymer (PDPPT-TT) [17]. This technique saves raw materials and controls film uniformity reliably, accurately, and reproducibly.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the device exhibited excellent shelf life and operating stabilities under ambient conditions. Finally, exceptionally high-gain inverters and functional ring oscillator devices on flexible substrates have been demonstrated [45,46].…”
mentioning
confidence: 99%